Exploring pathways into and out of amphetamine type stimulant use at critical turning points: a qualitative interview study. Issue 2 (4th May 2021) - Addison, Michelle; Kaner, Eileen; Spencer, Liam; McGovern, William; McGovern, Ruth; Gilvarry, Eilish; O'Donnell, Amy
ABSTRACT: Amphetamine Type Stimulants (ATS) are increasingly used drugs globally. There is limited evidence about what shapes ATS use at critical turning points located within drug using pathways. Using turning point theory, as part of a life course approach, the ATTUNE study aimed to understand which social, economic and individual factors shape pathways into and out of ATS use. Qualitative, semi-structured interviews ( n = 70) were undertaken with individuals who had used ATS, or had been exposed to them at least once. Our findings show that turning points for initiation were linked to pleasure, curiosity, boredom and declining mental health; increased use was linked to positive effects experienced at initiation and multiple life-stressors, leading to more intense use. Decreased use was prompted by pivotal events and sustained through continued wellbeing, day-to-day structure, and non-using social networks. We argue that the heterogeneity of these individuals challenges stereotypes of stimulant use allied to nightclubs and 'hedonism'. Further, at critical turning points for recovery, the use of services for problematic ATS consumption was low because users prioritised their alcohol or opioid use when seeking help. There is a need to develop service provision, training, and better outreach to individuals who need support at critical turning points.